PROSPECTS FOR THE DEVELOPMENT OF PRE-SCHOOL EDUCATION, SOCIAL-PEDAGOGICAL REQUIREMENTS FOR FIELD WORKERS - Alimova Zulfiya Karimovna (American Journals, 2023)
The article encourages the expansion of the state and non-state network of pre-school education today, the use of modern methods in teaching, the expression of the creativity of educators through the informatization of education, and the search for new, non-traditional forms and methods of interaction with children. It is thought that it consists of encouraging, as well as helping to increase children's interest in learning, activating their cognitive activity and developing the child in all aspects.
Keywords: education, organization, field, competence, decree, concept, spiritual, moral, ethical, aesthetic, physical, healthy, competition, state, non-state, multimedia, cognitive.